A ratiometric near-infrared fluorescence/photoacoustic dual-modal probe with strong donor dithienopyrrole for in vivo nitric oxide detection. (March 2023) - Xiao, Panpan; Liang, Mengke; Yang, Shuo; Sun, Ying; Li, Jia; Gu, Zhewei; Zhang, Ling'e; Fan, Quli; Jiang, Xiqun; Wu, Wei
Abstract: Integrating the imaging techniques of near-infrared fluorescence (NIRF) and photoacoustic (PA) can make up for each other and provide more useful medical information. Ratiometric imaging activated by disease-associated biomarkers can further augment imaging specificity. However, very few studies have employed the NIRF/PA dual-modal ratiometric imaging to improve the accuracy and specificity of disease diagnosis to date. In this paper, we present the synthesis of a nitric oxide (NO)-activated ratiometric NIRF/PA dual-modal nanoprobe RAPNP for in vivo NO imaging. The ratiometric imaging function was achieved jointly by a NO/acidity-responsive molecule DTP-BTDA and a nonresponsive fluorophore DTP-BBTD. In these fluorophores, the dithienopyrrole (DTP) moiety had strong electron-donating ability and imparted strong intramolecular charge transfer and relatively long emission wavelengths. The BTDA moiety in DTP-BTDA could be rapidly oxidized by NO under weak acidic environments, achieving the NIRF and PA signal activation. By using RAPNP as a contrast agent, we achieved the ratiometric detection of the endogenous NO in inflammatory bowel disease by NIRF/PA dual-modal imaging. This work provides the first case of the NIRF/PA dual-signal ratiometric probe for the real-time detection of NO in vivo.